2021
DOI: 10.3390/ijms22020951
|View full text |Cite
|
Sign up to set email alerts
|

An In Vivo Study of a Rat Fluid-Percussion-Induced Traumatic Brain Injury Model with [11C]PBR28 and [18F]flumazenil PET Imaging

Abstract: Traumatic brain injury (TBI) modelled by lateral fluid percussion-induction (LFPI) in rats is a widely used experimental rodent model to explore and understand the underlying cellular and molecular alterations in the brain caused by TBI in humans. Current improvements in imaging with positron emission tomography (PET) have made it possible to map certain features of TBI-induced cellular and molecular changes equally in humans and animals. The PET imaging technique is an apt supplement to nanotheranostic-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…The purification of crude [ 18 F]flumazenil was previously carried out using acetonitrile and water as the mobile phase [ 31 , 45 , 46 , 47 ]. However, acetonitrile is flammable, volatile, toxic, and must be removed during the purification process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The purification of crude [ 18 F]flumazenil was previously carried out using acetonitrile and water as the mobile phase [ 31 , 45 , 46 , 47 ]. However, acetonitrile is flammable, volatile, toxic, and must be removed during the purification process.…”
Section: Discussionmentioning
confidence: 99%
“…To further characterize the nature of GABA A receptor uptake, the effects of pre-treatment with 200 µg diazepam (BZR agonist) were studied in ex vivo autoradiography, and pre-treatment with 0.01–10 mg/kg diazepam for NanoPET/CT in vivo imaging. Pre-saturation studies have shown a high displaceable component for diazepam administration in the frontal cortex, cortex, amygdala, and hippocampus contrasted to [ 18 F]flumazenil, indicating that the structural modification of [ 18 F]flumazenil results will show in high affinity for GABA A /cBZRs (central benzodiazepine receptors) [ 23 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…including the benzodiazepine binding site. Upon receiving a signal from GABA, a chloride channel is opened that allows the entry of Cl-into the nerve cells, thereby reducing the intracellular potential of GABAA (type A) receptors [5,11,12]. GABA is the major inhibitory neurotransmitter in the central nervous system (CNS), and its receptors are widely distributed throughout the mammalian host.…”
Section: Introductionmentioning
confidence: 99%
“…Previous pre-clinical studies have suggested that an increased synaptic GABA concentration enhances the affinity of GABAA receptors for benzodiazepine ligands [16,17]. Flumazenil antagonizes the benzodiazepine binding site of the GABA/benzodiazepine receptor complex (BZR) in the CNS, thereby preventing chloride channel opening and inhibiting neuronal hyperpolarization [11,18]. Intravenous flumazenil treatment is used to recover from anesthesia and reduce the hypnotic and sedative effects of benzodiazepines via competitive inhibition at the benzodiazepine binding site on the GABAA receptor.…”
Section: Introductionmentioning
confidence: 99%